Research on key technology of vulnerability threat classification - Qi-xu LIU; Chong-bin ZHANG; Yu-qing ZHANG; Bao-feng ZHANG (Tongxin xuebao)
In order to solve the vulnerability assessment problem of vulnerability management,three attribute groups were selected to qualitatively evaluate vulnerability threat.After the selection of vulnerability attributes,analytic hierarchy process method was used to establish vulnerability classification model,which can divide vulnerabilities into four risk levels:critical,high,moderate and low.The method provides a reference for national standard,vulnerability management,vulnerability handling,risk assessment,risk mitigation,etc.